Fire effects on tree physiology. Issue 4 (22nd May 2019) - Bär, Andreas; Michaletz, Sean T.; Mayr, Stefan
Abstract : Summary: Heat injuries sustained in a fire can initiate a cascade of complex mechanisms that affect the physiology of trees after fires. Uncovering the exact physiological mechanisms and relating specific injuries to whole‐plant and ecosystem functioning is the focus of intense current research. Recent studies have made critical steps forward in our understanding of tree physiological processes after fires, and have suggested mechanisms by which fire injuries may interact with disturbances such as drought, insects and pathogens. We outline a conceptual framework that unifies the involved processes, their interconnections, and possible feedbacks, and contextualizes these responses with existing hypotheses for disturbance effects on plants and ecosystems. By focusing on carbon and water as currencies of plant functioning, we demonstrate fire‐induced cambium/phloem necrosis and xylem damage to be main disturbance effects. The resulting carbon starvation and hydraulic dysfunction are linked with drought and insect impacts. Evaluating the precise process relationships will be crucial for fully understanding how fires can affect tree functionality, and will help improve fire risk assessment and mortality model predictions. Especially considering future climate‐driven increases in fire frequency and intensity, knowledge of the physiological tree responses is important to better estimate postfire ecosystem dynamics and interactions with climate disturbances.